Critical Geography in the Age of the Social Justice Grift - Esson, James (ACME, 2026)
This commentary offers a personal reflection on what Critical Geography is, what it can be, and what it must be. Rather than defining the field in prescriptive terms, I reflect on how Critical Geography functions as a praxis and orientation, one that can be dangerous and must have consequences. I explore the risks and responsibilities of critical work in an era of performative allyship and institutional co-optation. The piece ends by calling for continued inward critique, arguing that Critical Geography must challenge the discipline itself if it is to avoid reproducing the very structures of power and exclusion it seeks to contest.